(untitled) (Journal of actual problems of jurisprudence, 2021)
According to the norms of family law, parents and persons replacing them acting as advocates of the interests of children, know better what is in the interests of the child and have practically unlimited powers in representing interests of the child. Various studies on the concept “interests of the child” have shown that the legal essence and content of it need to be described yet. Many scientists and practitioners emphasize on a one sided approach made toward the concept. And it is understandable since in all cases, with no exception, the interests of the child are considered from the point of social security, material protection, and enabling conditions for a decent life. The interests of the child: “this is a subjectively driven need of a child in favorable conditions of existence, which finds an objective expression in the realization by the parents of their rights and obligations provided for by family legislation”. The child is a separate person with own feelings and preferences. Interest is translated as “to have meaning” and despite the huge number of versatile approaches to this concept, in our context, interest should be understood as the real reason for the activity of social subjects, aimed at satisfying certain needs, underlying immediate motives, motives, ideas, etс., determined by the position and role of these subjects in the system of social relations. At the same time, the needs of modern children go beyond material world. Modern children, as noted above, consider their interests much more broadly and want to participate in solving problems that directly or indirectly affect their present or future life, which, in our opinion, significantly expands the content of the concept of «interests of the child.» Regarding Kazakhstan, it should be noted that the current legislation of the Republic of Kazakhstan enshrines the child’s right to freedom of speech and conscience, the right to information and participation in public life (Article 11 of the Law of the Republic of Kazakhstan «On the Rights of the Child»), which determines the republic’s desire to comply with the principles and provisions of the Convention, which was ratified in 1996 by Kazakhstan. The article is devoted to the issue of the need to revise approaches to the complexity of child rights by expanding the range of personal and political rights. Key words: child, right, obligation, children’s rights, state, state body.